Human colon carcinogenesis is associated with increased interleukin-17-driven inflammatory responses - Xie Z; Qu Y; Leng Y; Sun W; Ma S; Wei J; Hu J; Zhang X (Dove Medical Press, 2015)
Zhaohui Xie,1 Yine Qu,2 Yanli Leng,2 Wenxiu Sun,2 Siqi Ma,2 Jingbo Wei,2 Jiangong Hu,3 Xiaolan Zhang1 1Department of Gastroenterology, Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Histology and Embryology, Hebei United University School of Basic Medicine, Tangshan, Hebei, People’s Republic of China; 3Department of Pathology, the Second Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China Abstract: Inflammation is known to contribute to carcinogenesis in human colorectal cancer. Proinflammatory cytokine interleukin-17 (IL-17 or IL-17A) has been shown to play a critical role in colon carcinogenesis in mouse models. However, few studies have investigated IL-17A in human colon tissues. In the present study, we assessed IL-17-driven inflammatory responses in 17 cases of human colon adenocarcinomas, 16 cases of human normal colon tissues adjacent to the resected colon adenocarcinomas, ten cases of human ulcerative colitis tissues from biopsies, and eight cases of human colon polyps diagnosed as benign adenomas. We found that human colon adenocarcinomas contained the highest levels of IL-17A cytokine, which was significantly higher than the IL-17A levels in the adenomas, ulcerative colitis, and normal colon tissues (P<0.01). The levels of IL-17 receptor A (IL-17RA) were also the highest in human colon adenocarcinomas, followed by adenomas and ulcerative colitis. The increased levels of IL-17A and IL-17RA were accompanied with increased IL-17-driven inflammatory responses, including activation of extracellular signal-regulated kinase (ERK)1/2 and c-Jun N-terminal kinase (JNK) pathways, increase in expression of matrix metalloproteinase (MMP)9, MMP7, MMP2, B-cell lymphoma (Bcl-2), and cyclin D1, decrease in Bcl-2-associated X protein (BAX) expression, and increase in vascular endothelial growth factor (VEGF) and VEGF receptor (VEGFR) expression that were associated with increased angiogenesis. These findings suggest that IL-17 and its signaling pathways appear as promising new targets in the design and development of drugs for cancer prevention and treatment, particularly in colorectal cancer. Keywords: colitis, colorectal cancer, inflammation, IL-17